Take a Walk on the Shorts’ Side. ClujShorts International Short Film Festival, 3ʳᵈ edition (23-29 March) - IFTENE, Daniel (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
There’s no such thing as small festivals and movies. There are just events that keep growing and films that want to be great in spite of their brevity. This may be the alternate catch phrase for this year’s ClujShorts International Short Film Festival Edition, hosted in Cluj-Napoca, 2015 European Youth Capital.